(untitled) (Clinics, 2009)
BACKGROUND: Approximately one-half of Brazilian patients with hereditary hemochromatosis (HH) are neither homozygous for the C282Y mutation nor compound heterozygous for the H63D and C282Y mutations that are associated with HH in Caucasians. Other mutations have been described in the HFE gene as well as in genes involved in iron metabolism, such as transferrin receptor 2 (TfR2) and ferroportin 1 (SCL40A1). AIMS: To evaluate the role of HFE, TfR2 and SCL40A1 mutations in Brazilian subjects with HH. PATIENTS AND METHODS: Nineteen male subjects (median age 42 [range: 20-72] years) with HH were evaluated using the Haemochromatosis StripAssay A®. This assay is capable of detecting twelve HFE mutations, which are V53M, V59M, H63D, H63H, S65C, Q127H, P160delC, E168Q, E168X, W169X, C282Y and Q283, four TfR2 mutations, which are E60X, M172K, Y250X, AVAQ594-597del, and two SCL40A1 mutations, which are N144H and V162del. RESULTS: In our cohort, nine (47%) patients were homozygous for the C282Y mutation, two (11%) were heterozygous for the H63D mutation, and one each (5%) was either heterozygous for C282Y or compound heterozygous for C282Y and H63D. No other mutations in the HFE, TfR2 or SCL40A1 genes were observed in the studied patients. CONCLUSIONS: One-third of Brazilian subjects with the classical phenotype of HH do not carry HFE or other mutations that are currently associated with the disease in Caucasians. This observation suggests a role for other yet unknown mutations in the aforementioned genes or in other genes involved in iron homeostasis in the pathogenesis of HH in Brazil.